Reconocimiento de la Sarna polvosa (Spongospora subterranea f sp), en el cultivo de papa (Solanum tuberosum .L) en los sectores altos del cantón Espejo provincia del Carchi - Meneses Chunchir, Luis Javier (2018)
VII. SUMMARY The present investigation was carried out on localized potato crops, in the upper sectors of the Espejo canton, which surrounds the city of El Ángel, province of Carchi, in an altitude range that ranges between 3,200 and 3,320 meters above sea level. The proposed objectives were to recognize the presence of dusty scabies in potato crops, by using a methodology consisting of: application of surveys to a representative sample of the population, recognition and field trips; and, personal interviews with potato growers who have incidence of this disease. The technique used for the recognition of powdery scab in potato crops was based on the review and monitoring of the roots infected with this disease that prevents its normal vegetative development and consequently causes economic losses. As a result of the research carried out, it was found that at higher altitudes of the soils used for potato cultivation, the incidence of powdery scab increases. As also the use of seeds of potatoes considered resistant does not diminish this incidence. In the evaluation of the results, it was found that there is a direct relationship between the increase of the investigated disease; that is to say, that at higher altitudes of cultivated soils there is greater affectation of this disease. The present investigation aroused considerable interest from potato growers in the area, so it would be necessary to carry out further research in order to find a system for the prevention and control of powdery scab in potato crops.